Seismic response of rail counterweight systems in elevators. - Singh, Mahendra P.
The rail counterweight systems in building elevators are known to be susceptible to earthquake induced ground motions. Besides avoding costly repairs and economic disruptions, it is of special interest to maintain the functionality of the elevators in critical facilities such as hospitals during, and especially after, a strong earthquake event. This paper presents an approach to develop a realistic analytical model of these vulnerable systems to study their seismic response behaviour. The model includes the flexibilities of the guidance and supporting components of the counterweights in a systematic manner. Currently only the linear response behaviour is considered; however, the sources of non-linearities in the flexible components are clearly identified. The model considers the effect of the differential support motions from the building. Both the out of plane and in plane responses of the rail counterweight are studied and included in the stress calculations. Several sets of numerical results considering simultaneous action of the two orthogonal components of historic earthquakes are obtained to study the seismic response characteristics of the rail counterweight system.
Keywords: Elevators; Counterweight; Seismic response; Mechanical equipment; Earthquake effect on elevators; Elevator vibrations; Damage to elevators